Reconstruindo o Tekoha Guaiviry - Janaína Cardoso de Souza Ferreira (2015)
This paper is about a reconstruction of a tekoha kaiowá, in Mato Grosso do Sul, in the city of Aral Moreira: the tekoha Guaiviry. This is an area that was retaken by the Indians and it was reoccupied by the Kaiowá in November 2011. We realized that everything is still in a process of construction. We assumed that the relationship among families contribute and structure Guaiviry. The relationship of intimacy, mutuality and confidence among families happen by the domestic fire, in other words, inside the nuclear family. However, into the concept of domestic fire it might be included relatives by blood, friends and foster children. We noticed that the image of the praying man is central as much as for occupation, structuring and maintenance of tekoha. Guaiviry residents believe that their gains and permanence at this place of conflict is because of the praying man: Romildo Fernandes. Guaiviry is different in many aspects of the reserves and traditional paradigms found between the Kaiowá. Fernandes thinks it is wrong to pray in the seeds or in the products of the harvest. Thus, he doesn’t make some rituals that are traditional between the Kaiowá such as the avati kyry (the fresh corn ceremony), neither kunumi pepy (the ceremony of boys’ lips perforation). Fernandes explains that these rituals are dangerous for the good living between the Kaiowá. Following these tracks, we try to understand what are the main elements for having a good life between the Kaiowá. According to Romildo, the chichas, the songs and dances of guahu and kotyhu, the agriculture and the long prays of Thursdays are capable to achieve that goal. Thus, we introduced some hypothesis of interpretation to try to understand the socio-political and cosmological configuration of Guaiviry. The same way that Guaiviry reconstruction is in process, we believe that our interpretations can only be temporary. However, our effort seems to be valid as far as it shows us one of the possible ways to build a tekoha. What is in question is the construction of an idealized kind of life that was dreamed for generations, since their parents and grandparents were expelled of that tekoha. However, their process is made inside the social configuration that is typical of the Kaiowá and easily find in the intimacy and mutuality of the domestic fire, but they need to be forged in the construction of a totality called tekoha Guaiviry. This notion of totality is achieved through the rituals around the praying man in the fight against common enemies.